2010
DOI: 10.1097/qai.0b013e3181c5c81f
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Antiretroviral Use During Pregnancy and Infant Congenital Anomalies: The NISDI Perinatal Study

Abstract: Background We evaluated the association between maternal antiretrovirals (ARVs) during pregnancy and infant congenital anomalies (CAs), utilizing data from the NISDI Perinatal Study. Methods The study population consisted of first singleton pregnancies on study, ≥ 20 weeks gestation, among women enrolled in NISDI from Argentina and Brazil who delivered between September 2002 and October 2007. CAs were defined as any major structural or chromosomal abnormality, or a cluster of two or more minor abnormalities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…27 We observed an increasing trend in the rate of CAs from prior to 2002 through 2010, followed by a slight decline through 2012. The higher rates of CAs may reflect a real increase consistent with temporal trends demonstrated in various population studies, 2829 increased ascertainment given the study-required evaluation for anomalies, and longer follow-up than some studies.…”
Section: Discussionmentioning
confidence: 62%
“…27 We observed an increasing trend in the rate of CAs from prior to 2002 through 2010, followed by a slight decline through 2012. The higher rates of CAs may reflect a real increase consistent with temporal trends demonstrated in various population studies, 2829 increased ascertainment given the study-required evaluation for anomalies, and longer follow-up than some studies.…”
Section: Discussionmentioning
confidence: 62%
“…[5][6][7][8][9][17][18][19] The reasons underlying this variability may include the variable definition of birth defects, underreporting, the selective reporting of cases with defects, differential use of diagnostic techniques in the ascertainment of defects, and variable concomitant medication and substance exposure. 19 We also evaluated other potential predictors of birth defects, such as age, recent substance use, time since HIV diagnosis, CD4 cell count, body mass index, and coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…In general, registry data have provided reassuring data, showing no increased risk of major birth defects compared with the general population. 5 Cohort studies have reported more variable rates, [6][7][8][9] and it is particularly important to collect information on the drugs more recently introduced into clinical use, because only the older drugs have accumulated sufficient exposure data to rule out a major (usually defined as two-fold) increase in birth defects. 5 In a general scenario, characterised by the need to obtain the durable suppression of HIV replication, and prevent or circumvent the emergence of resistant strains, innovative drugs are regularly introduced into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Although so far was considered that administering the medication in the first trimester of pregnancy, when organogenesis occurs, could cause more side effects and malformations like hypospadias (21-23) than using them in the second or third trimester of pregnancy; this assumption was not confirmed (23)(24)(25).…”
Section: Discussionmentioning
confidence: 88%